ISSR fingerprinting of genetic diversity within and among Orobanche cumana wallr. populations from different countries - Ina Bivol (Acta et Commentationes: Ştiinţe Exacte şi ale Naturii)
Molecular genetic diversity was analysed for 23 Orobanche cumana populations from four countries using 13 ISSR markers. Descriptive population genetic statistics and AMOVA analysis revealed a marked degree of intrapopulation differentiation. PCA and UPGMA clustering showed a clear division into two main regional groups, i.e. the first group was more closely related to the Middle East and the second group belonged to Eastern Europe. The results of this research would suggest that the Moldavian, Bulgarian, and Romanian populations, which have many molecular markers in common, may share many genetic traits that indicate their monophyletic origin.